Primary leiomyoma of the ovary co-existing with serous cystadenofibroma - Case report - (:unkn) unknown (WILEY-BLACKWELL, 2005)
A 48-year-old woman with a 14 cm left ovarian mass had total abdominal hysterectomy and bilateral salpingo-oophorectomy. On cut section the tumor had a solid and a cystic component. There was a 2.5 cm nodule attached to the cyst wall. Sections taken from the solid component revealed a tumor composed of interlacing bundles of fusiform cells, resembling a leiomyoma. Smooth muscle actin positivity confirmed the diagnosis. Sections taken from the nodule in the cystic part revealed an adenofibroma. There was an SMA positive area in the cyst wall which we think is the possible origin of the leiomyoma. As far as we know, this is the first case of a co-existing leiomyoma and serous cystadenofibroma in the ovary, and we think it will broaden the histological spectrum of primary ovarian leiomyomas.
Keywords: leiomyoma; ovary; cystadenofibroma; SMOOTH-MUSCLE